2021
DOI: 10.1186/s12916-021-02063-9
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis related disability: a systematic review and meta-analysis

Abstract: Background The sustainable development goals aim to improve health for all by 2030. They incorporate ambitious goals regarding tuberculosis (TB), which may be a significant cause of disability, yet to be quantified. Therefore, we aimed to quantify the prevalence and types of TB-related disabilities. Methods We performed a systematic review of TB-related disabilities. The pooled prevalence of disabilities was calculated using the inverse variance he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 150 publications
0
44
0
3
Order By: Relevance
“…These values are in line with those estimated by Menzies et al, whonotably also taking conservative assumptions-estimated a mean increase of 383% (95% CI 154 to 755) in TB-related YLD globally, once morbidity experienced in the post-TB period had been added to that experienced during active disease. 35 While the degree of TB disability will vary between countries-particularly associated to their income 13 -our results point towards a vast amount of post-TB disability being overlooked among the 155 million TB survivors worldwide. 19 Our data suggest that post-TB morbidity is borne by a minority, with 94% of YLD faced by 20% of participants.…”
Section: Bmj Global Healthmentioning
confidence: 81%
See 1 more Smart Citation
“…These values are in line with those estimated by Menzies et al, whonotably also taking conservative assumptions-estimated a mean increase of 383% (95% CI 154 to 755) in TB-related YLD globally, once morbidity experienced in the post-TB period had been added to that experienced during active disease. 35 While the degree of TB disability will vary between countries-particularly associated to their income 13 -our results point towards a vast amount of post-TB disability being overlooked among the 155 million TB survivors worldwide. 19 Our data suggest that post-TB morbidity is borne by a minority, with 94% of YLD faced by 20% of participants.…”
Section: Bmj Global Healthmentioning
confidence: 81%
“…1 Those who survive TB disease face a considerable but under-recognised burden of ongoing morbidity including respiratory impairment, 2-5 psychosocial challenges and reduced health-related quality of life (HRQoL) after treatment completion. [6][7][8][9][10][11][12][13][14] Guidelines for TB management define 'treatment success' using microbiological outcomes and survival only, and measures of TB-associated morbidity remain solely focused on the period prior to and during treatment. 15 The most widely used measure of disease burdenassociated morbidity is the disability-adjusted life year (DALY).…”
Section: Introductionmentioning
confidence: 99%
“…What seems to be underreported is the impact of TB on the mental health of patients. According to a study by Alene et al [16], the prevalence of mental health impairment is found to be significantly high and they reported an incidence of 21.9% for mental disorders, second after respiratory impairment which was reported by 33.1% of patients. Depression, anxiety, post-traumatic stress disorder, and psychosis were seen among TB patients.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 1.5-million people died from tuberculosis (TB) disease in 2020, and TB is on course to retake its position as the largest cause of death by a single infectious agent [1]. Fuelled by ongoing transmission through exhaled or expectorated Mycobacterium tuberculosis ( Mtb ) bacteria, TB incidence is declining at a rate of 1-2% per annum, which is too slow given the risk and scale of mortality [1,2], lifelong impairment [3,4], poverty [5] and macro-economic consequences [6]. Problematically, most Mtb transmission in high incidence settings remains unaccounted for [3], with less than one-in-ten occurrences of TB explained by transmission from a known contact [7].…”
Section: Introductionmentioning
confidence: 99%